Existing Condition of Lubuk Larangan Management as a Form of Local Wisdom in Padang Sawah Village, Kampar Kiri Subdistrict, Kampar Regency, Riau Province - Tumanggor, Rosalina; Sumiarsih, Eni; Prianto, Eko (Jurnal Perikanan dan Kelautan, 2025)
Lubuk Larangan is a local wisdom initiative aimed at preserving fish resources and aquatic ecosystems. Natural resource and environmental management based on local wisdom, such as the Practices in Lubuk Larangan, Padang Sawah Village. This study aims to determine the current conditions of the Subayang River in Padang Sawah Village. This research was conducted in May–June 2024 in Padang Sawah Village, Kampar Kiri Subdistrict, Kampar Regency, Riau Province. The research method was a descriptive survey approach, utilizing data collection techniques such as observation, interviews, and physical-chemical parameter measurements. The materials and tools used were based on the parameters measured, namely physical-chemical and questionnaires. The results showed that Lubuk Larangan in Padang Sawah Village is still managed according to customary law by the ninik mamak. The community of Padang Sawah Village strongly supports the existence of Lubuk Larangan and wants to be more actively involved in its preservation. Lubuk Larangan in Padang Sawah Village has a very high level of community awareness, with a respondent participation index of 0.98. The water quality measurements obtained were a temperature of 29-30°C, brightness of 55-72 cm, depth of 1.7-2.2 m, current speed of 0.66-0.67 m/s, pH of 6.93-7.25, and dissolved oxygen of 3.40-4.10 mg/L. The management of Lubuk Larangan in Padang Sawah Village is supported by water quality that is still natural